Respiratory microbiome and metabolome features associate disease severity and the need for doxycycline treatment in children with macrolide-resistant Mycoplasma pneumoniae-mediated pneumonia - Liao, Wei-Chao; Li, Shiao-Wen; Hsing, En-Wei; Hsiao, Sung-Han; Chang, Ian Yi-Feng; Chen, Yin-Cheng; Chen, Yi-Yin; Pan, Yi-Jiun; Hsieh, Yu-Chia (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCommensal bacterial community along the upper respiratory tract functions against pathogens. The host determinants of Mycoplasma pneumoniae severity should be identified against the increasing threat of macrolide-resistant M. pneumoniae (MRMP) infection. We hypothesized that respiratory microbiome is involved in the clinical manifestations of M. pneumoniae infection.MethodsFrom 2017 to 2020, 92 children with MRMP-mediated pneumonia were enrolled among 845 children with community-associated pneumonia. Oropharyngeal samplings were collected within 48 h after admission. We compared respiratory microbiome and metabolites based on patients’ later development of prolonged fever and the need for doxycycline treatment (DT, n = 57) and the cured control without fever or doxycycline treatment (WDT, n = 35) by using 16S rRNA-based sequencing and untargeted metabolome analysis.ResultsSignificantly higher diversity and different respiratory microbiomes were evaluated in WDT patients in contrast to DT patients. Fusobacterium, Haemophilus, Gemella, Oribacterium, Actinomyces lingnae, Fusobacterium periodonticum, Gemella sanguinis, and Solobacterium moorei were inversely correlated with disease severity. We assumed that metabolites of divergent microbiomes were related to MRMP development. We identified 15 discriminative amino-acid- and fatty-acid-related metabolites in two groups. F. periodonticum abundance was negatively associated with an inflammatory metabolite: a platelet-activating factor. Fusobacterium and Oribacterium were related to the decrease in LysoPE(18:1(9Z)/0:0) and LysoPC(18:1(9Z)).ConclusionsMicrobiota dysbiosis with dysregulated inflammatory glycerolphospholipid-related metabolites was related to disease severity and the need for doxycycline treatment in children with MRMP-mediated pneumonia. Anaerobic bacteria metabolites and metabolic pathway could be beneficial therapeutic targets against M. pneumoniae infection.